LOW ENERGY AVAILABILITY AND RISK OF EATING DISORDERS IN FEMALE ATHLETES (Interdisciplinary Studies Journal, 2026)
Low energy availability (LEA) is a critical factor in female athlete health, associated with significant physiological, metabolic, and psychological consequences. In sports valuing body aesthetics or strict weight control, LEA can result from calorie restriction, overtraining, or both, compromising hormonal, reproductive, cognitive, and immune functions. This review critically discusses evidence linking LEA and eating disorder (ED) risk in female athletes. Publications indexed between 2005 and 2024 were consulted. Findings suggest that while not all studies demonstrate statistically significant correlations between LEA and ED, consistent evidence indicates energy imbalance encourages eating behaviour changes, particularly with body dissatisfaction, performance pressure, and sociocultural influences like social media. Relevant side effects include sleep deprivation, mood swings, neuroendocrine dysregulation, and reduced bone mass. The literature highlights the need for preventive strategies emphasising nutritional education and psychological support integrated into sports planning. LEA is a multifactorial condition requiring early recognition and interdisciplinary interventions to preserve female athletes’ physical and mental well-being, especially in sports with high aesthetic or performance demands.
Keywords: Eating Disorders; Low Energy Availability; Female Athletes; Body Image